2014
DOI: 10.1371/journal.pone.0113357
|View full text |Cite|
|
Sign up to set email alerts
|

Serologically Defined Variations in Malaria Endemicity in Pará State, Brazil

Abstract: BackgroundMeasurement of malaria endemicity is typically based on vector or parasite measures. A complementary approach is the detection of parasite specific IgG antibodies. We determined the antibody levels and seroconversion rates to both P. vivax and P. falciparum merozoite antigens in individuals living in areas of varying P. vivax endemicity in Pará state, Brazilian Amazon region.Methodology/Principal FindingsThe prevalence of antibodies to recombinant antigens from P. vivax and P. falciparum was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 46 publications
3
46
0
Order By: Relevance
“…The results showed poor antigenicity of allelic variant antigens representing both block 2 and block 10 of PvMSP-1 in opposition to the high antigenicity of the conserved C-terminal, PvMSP-1 19 . The high magnitude of IgG response to the conserved C-terminal domain of the PvMSP-1 protein that is the only fragment that remains attached to the merozoite surface during erythrocyte invasion [18, 19] is an expected result and confirms previous data from several serological studies conducted in different epidemiological settings in the Brazilian endemic area [2026]. …”
Section: Discussionsupporting
confidence: 84%
“…The results showed poor antigenicity of allelic variant antigens representing both block 2 and block 10 of PvMSP-1 in opposition to the high antigenicity of the conserved C-terminal, PvMSP-1 19 . The high magnitude of IgG response to the conserved C-terminal domain of the PvMSP-1 protein that is the only fragment that remains attached to the merozoite surface during erythrocyte invasion [18, 19] is an expected result and confirms previous data from several serological studies conducted in different epidemiological settings in the Brazilian endemic area [2026]. …”
Section: Discussionsupporting
confidence: 84%
“…Seroprevalence (SP) is then the percentage of seropositive individuals in the sample and embodies information over currently infected and recently exposed individuals. As expected, SP estimates are typically higher than those for PR measured in the same sample [ 1 , 7 ]. Although overcoming some of the shortcomings of PR and EIR, SP does not reflect the dynamics of malaria transmission directly.…”
Section: Introductionsupporting
confidence: 57%
“…Several studies have shown the utility of SCR as a malaria epidemiological tool with some demonstrating good agreement between this measure and EIR [ 1 ] and others detecting historical changes in transmission that otherwise would not have been possible with other measures of transmission [ 4 , 7 - 9 ]. Whilst the evidence for using serology as an adjunct epidemiological marker for malaria transmission is growing, there has been no formal examination of samples size considerations for SP and SCR as primary endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…Several cross-sectional sero-epidemiological studies in Amazonian countries have reported the association of antibody responses with previous malaria infections by P. vivax and P. falciparum (3,18,25,26). However, because these previous studies relied on individual recall of past malarial infection, they could not reliably date or confirm past infections.…”
Section: Discussionmentioning
confidence: 99%